SPECT/CT imaging of EGFR-positive head and neck squamous cell carcinoma patient-derived xenografts with 203Pb-PSC-panitumumab in NRG mice - Nasim Sarrami; Bryce Nelson; Samantha Leier; John Wilson; Conrad Chan; Jalna Meens; Teesha Komal; Laurie Ailles; Melinda Wuest; Michael Schultz; Afsaneh Lavasanifar; Raymond M. Reilly; et al. (SpringerOpen, 2024)
Abstract Background The objective of this research was the development and evaluation of 203Pb-labelled panitumumab (203Pb-PSC-panitumumab) as an immuno-SPECT radioligand for the detection of EGFR + head and neck squamous cell carcinoma (HNSCC) in a patient-derived xenograft (PDX) mouse model. The 51.9 h physical half-life and favourable γ-emission (279 keV; 81%) of 203Pb offer an excellent opportunity for developing immuno-SPECT radioligands. Moreover, 203Pb has a complementary therapeutic radionuclide (212Pb), making 203Pb and 212Pb an ideal matched radiotheranostic pair. Results Radiolabeling of panitumumab was performed at a pH of 5.0 and room temperature for 5-10 min with [203Pb]Pb(OAc)2, and the incorporation efficiency was determined using radio-TLC. 203Pb-PSC-panitumumab (~ 10 MBq, 140 μl of saline) was injected into the tail vein of NRG mice bearing subcutaneous (s.c.) HNSCC patient-derived xenografts (PDX). SPECT/CT images were acquired at 48 and 120 h post-injection. For biodistribution studies, mice were euthanized five days after 203Pb-panitumumab injection. The tumour and normal tissues were collected and weighed, and uptake of 203Pb was measured in a γ-counter. The uptake was calculated as the percent injected dose per gram of each tissue (ID%/g). Blocking experiments were performed by pretreating a group of mice (n = 5) with 1 mg of panitumumab 1 h before administering 203Pb-PSC-panitumumab. 4-5 chelators of a new lead-specific chelator (PSC) were attached per antibody; radiolabeling efficiency was 99.2 ± 0.7%. The isolated radiochemical yield of 203Pb-PSC-panitumumab was 41.4 ± 8% (n = 5), and the molar activity was 1.2 ± 0.35 GB/mg. SPECT imaging and biodistribution confirmed high accumulation and retention of 203Pb-PSC-panitumumab in the tumour (26% ID/g) at 120 h post-injection (p.i.), which could be reduced to 6.2%ID/g at 120 h p.i. by predosing with panitumumab (1 mg) confirming EGFR specificity of 203Pb-PSC-panitumumab uptake. Conclusions Panitumumab was successfully and reproducibly labelled with 203Pb in high radiochemical purity using the chelator PSC-NCS. 203Pb-PSC-panitumumab was specifically accumulated and retained in EGFR + tumours in NRG mice with s.c. HNSCC PDX. 203Pb-PSC-panitumumab is a suitable immuno-SPECT radioligand for imaging EGFR + tumours and has great potential for combining with 212Pb-PSC-panitumumab in a radiotheranostic strategy for imaging and treating HNSCC.